An investigation into the spectral transfer function and characterization of a terrestrial solar-blind ultraviolet electro-optical system - Leuschner, Friedrich Wilhelm (University of Pretoria, 2022)
Dissertation (MEng (Electronic Engineering))--University of Pretoria, 2015.